2020
DOI: 10.1002/ijfe.1825
|View full text |Cite
|
Sign up to set email alerts
|

OPECmeetings, oil market volatility and herding behaviour in the Saudi Arabia stock market

Abstract: We investigate the influence of oil market volatility and hand‐picked OPEC meetings data on herding tendency in the Saudi equity market. Our results show the presence of significant herding behaviour in the Saudi market; surprisingly this herding behaviour is independent of oil market volatility. Importantly, we find herding on and around the OPEC meeting days however this is only limited to a period of high global uncertainty that is, during the Global Financial Crisis period (GFC) of 2008–2010. However, when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 52 publications
1
12
0
1
Order By: Relevance
“…Maghyereh et al (2020) found that herding in the UAE stock markets is more pronounced during market declines and high volatility regimes. Finally, Gabbori et al (2021) found significant herding behaviour in the Saudi market around OPEC meeting days.…”
Section: Literature Reviewmentioning
confidence: 88%
See 1 more Smart Citation
“…Maghyereh et al (2020) found that herding in the UAE stock markets is more pronounced during market declines and high volatility regimes. Finally, Gabbori et al (2021) found significant herding behaviour in the Saudi market around OPEC meeting days.…”
Section: Literature Reviewmentioning
confidence: 88%
“…However, this is true only in lowvolatility regimes and herding is still significant despite speculation in energy markets when equity volatility is high. Youssef and Mokni (2018), Ulussever and Demirer (2017), Demir and Solakoglu (2016), Chaffai and Medhioub (2018), Maghyereh et al (2020), andGabbori et al (2021) focused on the herding behavior of GCC countries. Youssef and Mokni (2018) found that herding has a positive influence on associations among financial markets in the region.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several studies explore herding in various markets, including equities (Hwang and Salmon, 2004;Demirer and Kutan, 2006;Tan et al, 2008;Choi and Sias, 2009;Chang, 2010;Yao et al, 2014;Galariotis et al, 2015;Clements et al, 2017;Vo and Phan, 2019;Gabbori et al, 2020;Munkh-Ulzii et al, 2020;Alhaj-Yaseen and Rao, 2019), bonds (Galariotis et al, 2016;Cai et al, 2019), commodities (Babalos and Stavroyiannis, 2015;Kumar et al, 2020;J unior et al, 2020;Youssef, 2020), real estate , mutual funds (Wermers, 1999;Walter and Moritz, 2006;D'Arcangelis and Rotundo, 2019) and cryptocurrency (Bouri et al, 2019;Ballis and Drakos, 2020; under various conditions and during crisis periods. However, fewer studies examine herding behaviour in Islamic markets.…”
Section: Introductionmentioning
confidence: 99%
“…The Gulf countries rely heavily on oil revenue as their main source of income, making them particularly vulnerable to external shocks, which could threaten their financial stability (Al-Maadid et al, 2020), and the GCC markets are strongly linked with movements of the oil prices and oilrelated news (Mohanty et al, 2011;Alqahtani et al, 2019;Cheikh et al, 2021). Gabbori et al (2020) find herding around OPEC meetings days. Ulussever and Demirer (2017) find that oil prices significantly influence herding in Gulf equity markets.…”
Section: Introductionmentioning
confidence: 99%
“…Oil is one of the most important commodities in the world, and it is one of the most pivotal raw materials of industry (Chen, Li, Xiao, & Wen, 2020; Kilian, 2009; Peng, Wen, & Gong, 2020; Xiao, Hu, Ouyang, & Wen, 2019). As we all know, oil is not only a natural resource, but also a financial asset when trading in the futures market (see Gabbori, Awartani, Maghyereh, & Virk, 2020; Lin & Li, 2015; Tang, Xiao, Wahab, & Ma, 2020; Wang, Liu, & Wu, 2017). Therefore, it is exceedingly crucial to study the relationship between crude oil price and economic conditions or financial markets.…”
Section: Introductionmentioning
confidence: 99%